2021
DOI: 10.3389/fcell.2021.757068
|View full text |Cite
|
Sign up to set email alerts
|

FSTL1-USP10-Notch1 Signaling Axis Protects Against Cardiac Dysfunction Through Inhibition of Myocardial Fibrosis in Diabetic Mice

Abstract: The incidence of type 2 diabetes mellitus (T2DM) has been increasing globally, and T2DM patients are at an increased risk of major cardiac events such as myocardial infarction (MI). Nevertheless, the molecular mechanisms underlying MI injury in T2DM remain elusive. Ubiquitin-specific protease 10 (USP10) functions as a NICD1 (Notch1 receptor) deubiquitinase that fine-tunes the essential myocardial fibrosis regulator Notch signaling. Follistatin-like protein 1 (FSTL1) is a cardiokine with proven benefits in mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 61 publications
(87 reference statements)
0
25
0
Order By: Relevance
“…The UPS family possesses an important function in maintaining protein homeostasis and is associated with diabetes-related complications (21,22). In the study of type 2 diabetes, Forand et al found that inhibiting the dissociation of USP7/Insulinreceptorsubstrate1 (IRS1) and preventing the ubiquitination of IRS1 had a protective effect on diabetic mice (23).…”
Section: Discussionmentioning
confidence: 99%
“…The UPS family possesses an important function in maintaining protein homeostasis and is associated with diabetes-related complications (21,22). In the study of type 2 diabetes, Forand et al found that inhibiting the dissociation of USP7/Insulinreceptorsubstrate1 (IRS1) and preventing the ubiquitination of IRS1 had a protective effect on diabetic mice (23).…”
Section: Discussionmentioning
confidence: 99%
“…T2DM patients have an increased risk of several cardiac disorders, including myocardial infarction (MI) [ 175 ]. Interestingly, in T2DM models induced by a high-fat diet or leptin receptor deficiency, the left ventricular rejection fraction and left ventricular fraction shortening were decreased, while the ventricular internal diameter at end-diastole and the left ventricular internal diameter at end-systole were increased [ 176 ]. Moreover, additional treatment with MI caused further alterations in these indices [ 176 ].…”
Section: Diabetes-associated Disordersmentioning
confidence: 99%
“…Interestingly, in T2DM models induced by a high-fat diet or leptin receptor deficiency, the left ventricular rejection fraction and left ventricular fraction shortening were decreased, while the ventricular internal diameter at end-diastole and the left ventricular internal diameter at end-systole were increased [ 176 ]. Moreover, additional treatment with MI caused further alterations in these indices [ 176 ]. In T2DM models, increases were found in α-smooth muscle actin, a myofibroblast marker, and the fibrosis markers collagen type I and matrix metalloprotease 9, suggesting the occurrence of cardiac fibrosis [ 176 ].…”
Section: Diabetes-associated Disordersmentioning
confidence: 99%
“…While moderate physical activity increases the coronary arteries and capillary density in wild-type mice and capillary density does not change in mice without Notch3 ( Ragot et al, 2016 ). Increased exercise (56–66% of VO 2max for 4 weeks)-induced Follistatin-like protein 1 (FSTL1) secretion through the FSTL1-USP10-Notch1 signaling axis has been reported to inhibit myocardial fibrosis in diabetic rats ( Xi et al, 2016 ; Lu et al, 2021 ) ( Table 2 ). Aerobic exercise (75% of maximal metabolic for 12 weeks) significantly reduces systolic blood pressure, which is independently correlated with skin capillary density and vascular density in humans.…”
Section: Extracellular Apoptosis Signaling Pathwaysmentioning
confidence: 99%
“…Increase (Burgess et al, 2001;Burgess et al, 2002;Brancaccio et al, 2006;Wilkinson et al, 2008;Manso et al, 2009;Flueck et al, 2011;Muthuchamy et al, 2012;Li et al, 2013;Watson and Baar, 2014;Graham et al, 2015a;Graham et al, 2015b;Franchi et al, 2018) Aerobic exercise 56-66% of VO2max for 4 weeks FSTL1-USP10-Notch1, Notch3, sFLT1 Increase (Xi et al, 2016;Lu et al, 2021) Aerobic exercise 75% of maximal metabolic for 12 weeks Notch1/Akt/eNOS Increase Liang et al (2021) Aerobic exercise 75% of VO2max for 6 weeks SIRT1, MnSOD, PGC-1α, HIF-1α, VEGF, catalase Increase (Rinaldi et al, 2013;Wen et al, 2019) Swimming training 48-72% of VO2max for 5 weeks…”
Section: Changes Referencementioning
confidence: 99%